PENDAMPINGAN BERKELANJUTAN UNTUK PRODUKSI DAN PENETAPAN HARGA - Simanjuntak, Nurlinawati; Manurung, Herta; Siallangan, Dahlia; Purba, Hotlan; Simanjuntak, Erlianti; Pinem, Elsameda Chairani; P Tambunan, Samuel (Smart Education, 2025)
Abstract: Community service conducted by the Faculty of Economics, Unita, with the Baion